Vacuolar (H+)‐ATPase subunit c is essential for the survival and systemic RNA interference response in Locusta migratoria. Issue 4 (20th January 2022) - Shi, Xuekai; Liu, Xiaojian; Cooper, Anastasia MW; Silver, Kristopher; Merzendorfer, Hans; Zhu, Kun Yan; Zhang, Jianzhen
Abstract: Background: Vacuolar (H + )‐ATPase (V‐ATPase) is a multi‐subunit enzyme that hydrolyzes adenosine triphosphate (ATP) to transport protons across a cellular membrane, and it plays an important role in numerous biological processes, including in growth, development and immune responses. The c subunit of V‐ATPase is a highly conserved subunit of the rotatory proteolipid ring that is required for binding and transporting protons. To date, there are only a few published reports on V‐ATPase‐c functions in insects. Results: We identified and characterized the V‐ATPase‐c gene in Locusta migratoria, one of the most destructive agricultural insect pests in the world. LmV‐ATPase‐c was predominately expressed in Malpighian tubules of nymphs, followed by the hindgut and ovary, while the other tissues showed relatively low expression levels. Silencing of LmV‐ATPase‐c caused severe molting defects in nymphs and a high mortality rate of > 90%. Histological staining and microscopic examination of sections from the abdominal cuticle revealed the absence of newly formed cuticle in nymphs that were injected with dsLmV‐ATPase‐c . In addition, silencing of LmV‐ATPase‐c transcript levels significantly impaired RNA interference (RNAi) efficiency of a reporter gene. By quantifying double‐stranded RNA (dsRNA) amounts by quantitative polymerase chain reaction (PCR), we found that RNAi against LmV‐ATPase‐c provoked a dramatic accumulation of dsRNA in the endosomes of epidermal and midgut cells of Locusta migratoria . Conclusion: Our results indicate that LmV‐ATPase‐c is indispensable for the formation of new cuticle during the molting process and has pivotal functions in dsRNA escape from endosomes. LmV‐ATPase‐c might be a valuable target for developing new strategies for insect pest management. © 2022 Society of Chemical Industry. Abstract : This article reports molecular properties and biological roles of the vacuolar (H + )‐ATPase subunit c gene in the formation of new cuticle and endosomal escape of double‐stranded RNA in Locusta migratoria .